(untitled) (Journal of the Society for Musicology in Ireland, 2020)
In January 2015, Jennifer Walshe, a contemporary Irish composer, in collaboration with a handful of Irish artists, musicians, and composers, published Aisteach, a fictional history of an Irish avant-garde. The contemporary artists invented an ‘archive’ of Irish avant-gardists, who allegedly lived in the nineteenth, twentieth, and twenty-first centuries, writing their histories and composing works attributed to them. The creators then built a website that includes articles on the imaginary artists, recordings of their works, and images of their art, among other resources. Aisteach continues to expand as more people contribute to it; the most recent exhibition, which occurred in Sligo, Ireland in September 2018, introduced more imaginary artists into Irish history. Including many female and LGBTQ figures, Aisteach constructs a more diverse and inclusive history of Irish art and music that in turn casts a new light both on the real historical past and the present musical and political scenes. Through this invented tradition, the Aisteach creators also evoke alternative memories that fill in gaps in their nation’s compositional history, enable future generations of artists in Ireland, and work through their cultural inheritance to reshape and, in some cases, reaffirm conceptions of Irishness.